Mouse-adapted SARS-CoV-2 protects animals from lethal SARS-CoV challenge - Antonio Muruato; Michelle N. Vu; Bryan A. Johnson; Meredith E. Davis-Gardner; Abigail Vanderheiden; Kumari Lokugamage; Craig Schindewolf; Patricia A. Crocquet-Valdes; Rose M. Langsjoen; Jessica A. Plante; Kenneth S. Plante; Scott C. Weaver; et al. (PLoS Biology, 2021)
The emergence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has resulted in a pandemic causing significant damage to public health and the economy. Efforts to understand the mechanisms of Coronavirus Disease 2019 (COVID-19) have been hampered by the lack of robust mouse models. To overcome this barrier, we used a reverse genetic system to generate a mouse-adapted strain of SARS-CoV-2. Incorporating key mutations found in SARS-CoV-2 variants, this model recapitulates critical elements of human infection including viral replication in the lung, immune cell infiltration, and significant in vivo disease. Importantly, mouse adaptation of SARS-CoV-2 does not impair replication in human airway cells and maintains antigenicity similar to human SARS-CoV-2 strains. Coupled with the incorporation of mutations found in variants of concern, CMA3p20 offers several advantages over other mouse-adapted SARS-CoV-2 strains. Using this model, we demonstrate that SARS-CoV-2–infected mice are protected from lethal challenge with the original Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV), suggesting immunity from heterologous Coronavirus (CoV) strains. Together, the results highlight the use of this mouse model for further study of SARS-CoV-2 infection and disease. Studying cross-protection from different coronaviruses is important to inform the research for a universal vaccine. This study uses a mouse-adapted SARS-CoV-2 strain to show that it confers protection from SARS-CoV challenge, suggesting possible immunity from heterologous challenge following natural infection.